2018
DOI: 10.1007/s10787-018-0499-4
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-β inhibits inflammatory responses mediators via suppression of iNOS signaling pathway in PBMCs from patients with primary Sjögren’s syndrome

Abstract: Our findings highlight a consistent ex vivo inhibitory effect of IFN-β on pro-inflammatory cytokine production and NO pathway in pSS patients. Our data suggest that IFN-β could represent a potential candidate for targeting inflammation during pSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…However, the results of Benchabane's group suggested that IFN-β restored immune balance between inflammatory and anti-inflammatory responses by reducing pro-inflammatory cytokines in peripheral blood mononuclear cells from SS patients. Therefore, it seemed that IFN-β had beneficial impact in SS 47. Therefore, further studies are needed to uncover the exact role and precise mechanisms of IFN-β in SS.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of Benchabane's group suggested that IFN-β restored immune balance between inflammatory and anti-inflammatory responses by reducing pro-inflammatory cytokines in peripheral blood mononuclear cells from SS patients. Therefore, it seemed that IFN-β had beneficial impact in SS 47. Therefore, further studies are needed to uncover the exact role and precise mechanisms of IFN-β in SS.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, recent research findings highlight a consistent ex vivo inhibitory effect of IFN- β on proinflammatory cytokine production and NO pathway in pSS patients. These data suggest that IFN- β could represent a potential candidate for targeting inflammation during pSS [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of type I IFNs in Sjögren’s syndrome may be subtype specific. IFN-β may reduce the expression of proinflammatory mediators in peripheral blood mononuclear cells isolated from patients with Sjögren’s syndrome 60. Like SLE, patients with Sjögren’s syndrome can be stratified by those who do and do not have an IFNGS.…”
Section: Type I Ifns In Autoimmune Diseasesmentioning
confidence: 99%